Penguatan Karakter Kinerja Kepemimpinan Siswa SMA Negeri I Pariangan Kabupaten Tanah Datar - Ismira, Ismira (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
This article was written as a reflection of the community service activities of Adzkia University lecturers. This service is carried out in the context of basic level leadership training activities for the OSIS team (Intra-School Student Organization) and class leaders at Senior High School Pariangan District, Tanah Datar Regency, West Sumatra Province, Indonesia. The topic presented was entitled